Leading directions and tendencies of research of the problem of professional training of future primary school teachers in Ukraine (Pedagogy of Higher and Secondary Education, 2012)
Zhelanova V. V. Leading directions and tendencies of research of the problem of professional training of future primary school teachers in Ukraine. In the article basic directions and tendencies of research of problem of professional preparation of future teacher of initial classes are exposed in Institute of higher in a modern period which coincides with introduction of leading ideas of Bolonskoy convention in the system of higher education in Ukraine.
Keywords: professionally meaningful qualities; readiness of future teacher to the of professional activity; polyparadyhmalnost; integration of scientific approaches; reflection orientation; practical orientation of education